Effects of psychological eating behaviour domains on the association between socio-economic status and BMI. Issue 15 (24th July 2017) - Löffler, Antje; Luck, Tobias; Then, Francisca S; Luck-Sikorski, Claudia; Pabst, Alexander; Kovacs, Peter; Böttcher, Yvonne; Breitfeld, Jana; Tönjes, Anke; Horstmann, Annette; Löffler, Markus; Engel, Christoph; et al.
Abstract: Objective: The current study investigates potential pathways from socio-economic status (SES) to BMI in the adult population, considering psychological domains of eating behaviour (restrained eating, uncontrolled eating, emotional eating) as potential mediators stratified for sex. Design: Data were derived from the population-based cross-sectional LIFE-Adult-Study. Parallel-mediation models were conducted to obtain the total, direct and indirect effects of psychological eating behaviour domains on the association between SES and BMI for men and for women. Setting: Leipzig, Germany. Subjects: We studied 5935 participants aged 18 to 79 years. Results: Uncontrolled eating mediated the association between SES and BMI in men only and restrained eating in both men and women. Emotional eating did not act as mediator in this relationship. The total effect of eating behaviour domains on the association between SES and BMI was estimated as β =−0·03 (se 0·02; 95 % CI −0·062, −0·003) in men and β =−0·18 (se 0·02; 95 % CI −0·217, −0·138) in women. Conclusions: Our findings do not indicate a strong overall mediation effect of the eating behaviour domains restrained eating, uncontrolled eating and emotional eating on the association between SES and BMI. Further research on other pathways of this association is strongly recommended. Importantly, our findings indicate that, independent from one's social position, focusing on psychological aspects in weight reduction might be a promising approach.